Investigating the feasibility of developing a collective action for biological control of fall armyworm among smallholder farmers in rural communities of Zambia - Léna, Durocher‑Granger; Sara, Fiorito; Mudenda, Sibajene Kambanja; Chiboola, Milimo Mildred; Kansiime, Monica K.; Ludwig, David; Leeuwis, Cees (CABI Agriculture and Bioscience, 2023)
Background Fall armyworm, Spodoptera frugiperda, an alien invasive pest from the Americas, was detected in Zambia late 2016 and since has caused significant losses on maize threatening livelihood and food security. Individually, farmers continue to rely on synthetic pesticides, a reactive measure to manage new invasive insect pests, posing risks to human health, the environment and biodiversity. Biological control has been proven to be an efficient, cost effective and safe method for pest and disease management, and when adopted collectively, its effectiveness can increase. In addition, collective action has been acknowledged to be a critical component for invasive species management, but is still poorly studied in low- and middle-income countries (LMIC) where the national plant health system, in-place to prevent and manage biological invasions, is limited. Methods To study the feasibility of creating a collective action to promote biological control for fall armyworm among smallholder farmers in rural Zambia and the social and institutional conditions needed for it to be successful and sustainable, we conducted focus group discussions and in-depth interviews in two districts with maize smallholder farmers. Our model to assess the results applies both Ostrom’s 8 Design Principles for a community-based management of common-pool resources and criteria of an agricultural innovation that meet the community’s requirements, and also pays attention to the exchange and brokering processes needed to match the two. Results Our results showed that some conditions are already in place to support a collective action to manage fall armyworm such as matching rules to local conditions, collective-choice arrangement, conflict-resolution mechanism and minimal recognition of rights to organize which are supported by traditional leadership of the communities. However other conditions would need to be strengthened for the collective pest management to be sustainable. The most important criteria for a pest management innovation selected by participants from both districts, in no specific order, were price, efficacy, recommended by agrodealer/extension officer and immediate action. Conclusions This study fills a gap in understanding social and institutional conditions in LMIC needed to sustain a collective action that aim at controlling a highly mobile and invasive pest. Our study emphasizes the need to redefine technologies and dissemination in terms of supporting the processes of co-designing innovation based on social and ecological conditions.